Corruption perceptions and entrepreneurial intentions in a transitional context - The case of rural Bulgaria - Diana Traikova; Tatiana S. Manolova; Judith Möllers; Gertrud Buchenrieder (Journal of Developmental Entrepreneurship, 2017)
In this study, we augment Ajzen's Theory of Planned Behavior (TPB) with an institutional embeddedness logic to develop and test a mediated model of the effects of perceived corruption on attitudes, social norms and perceived behavioral control, which in turn determine entrepreneurial intentions. We test our three hypotheses on a sample of 231 aspiring entrepreneurs seeking to start a non-farm business in three rural regions of Bulgaria. In our exploratory case study, we find that corruption perceptions are partially mediated by entrepreneurial attitudes and perceived control, but not by social norms. Corruption perceptions are positively associated with entrepreneurial intentions, indicative of the deeply rooted social acceptance of corruption in many transition economies. Theoretical, practitioner and public policy implications are discussed.
Keywords: 330; corruption perceptions; entrepreneurial intentions; mediation; TPB; transition economies; rural entrepreneurship